2013
DOI: 10.1186/1475-2891-12-52
|View full text |Cite
|
Sign up to set email alerts
|

Assessing dietary intake among infants and toddlers 0–24 months of age in Baltimore, Maryland, USA

Abstract: ObjectiveTo characterize food and nutrient intake and develop a population-specific food list to be used as a comprehensive dietary assessment tool for Baltimore infants and toddlers aged 0–24 months. The data were used to inform the Growing Leaps and Bounds (GLB) program, which promotes early obesity prevention among Baltimore infants and toddlers.Research methods & proceduresA cross-sectional dietary survey using 24-hour recalls among randomly selected primary caregivers of infants and toddlers was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…However, 24‐h recalls have been validated against weighed food records and shown to be accurate . They have been used previously in infant feeding research , although one review study found weighed food records to be the most accurate compared to the doubly‐labelled water method (a measurable biomarker) with respect to recording energy intake in younger children aged 6 months to 4 years of age .…”
Section: Discussionmentioning
confidence: 99%
“…However, 24‐h recalls have been validated against weighed food records and shown to be accurate . They have been used previously in infant feeding research , although one review study found weighed food records to be the most accurate compared to the doubly‐labelled water method (a measurable biomarker) with respect to recording energy intake in younger children aged 6 months to 4 years of age .…”
Section: Discussionmentioning
confidence: 99%
“…Five percent of the toddlers had an intake above the upper limit of the acceptable macronutrient distribution range, which is 20 PE%. In a small recent study from Baltimore, MD, the mean (6SD) protein content in the diet of 7-to 12-mo-old infants was 9.7 6 2.8 PE% and 13.3 6 3.6 PE% in the 13-to 24-mo age group (8).…”
Section: Protein Content Of Foods For Infants and Toddlersmentioning
confidence: 99%
“…The 24hDR is a common tool used in many studies to assess the dietary intake of infants and young children [28]. This tool is useful because of its short administration time and low need for respondent literacy.…”
Section: Assessment Of Dietary Intakementioning
confidence: 99%